THE USE OF MOODLE IN ENGLISH LANGUAGE LEARNING DURING THE PANDEMIC: THE STUDENTS VOICE - Nausa Revy Maulana; Alies Poetri Lintangsari (Faculty of Teacher Training and Education, Universitas Sriwijaya, 2021)
During the emergency remote learning, the role of the Learning Management System is significant to support the teaching and learning process. Many universities utilized the Moodle based LMS to assist students and teachers in the teaching and learning process including Universitas Brawijaya that used Virtual Learning Management (VLM). VLM is highly suggested to be used by the lecturers since it can be accessed free as supported by the University, nonetheless, students claimed that the use of VLM is sometimes problematic. To address the students’ voice toward the use of VLM, this research aims to describe the students' attitude towards the use of VLM as an online learning platform. In this research, quantitative method with a survey design was chosen. Instrument used in this study was questionnaire adapted to the works of Srichanyachon (2014), Munasinghe and Wijewardana (2016), and Putri and Sari (2020). There were 100 students participating in this study; they consist of 79 female students and 21 male students. The data were analyzed descriptively. The result of the study revealed that the use of platforms such as LMS in the COVID 19 era is indispensable and makes it a very effective platform to use. The students gave a positive attitude to the use of Moodle with a mean score of 3.58.